2016
DOI: 10.1007/s10895-016-1876-2
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-Containing Analog of Dibenzoylmethanate of Boron Difluoride: Luminescence, Structure, Quantum Chemical Modeling, and Delay Fluorescence

Abstract: Boron difluoride of 3-amino-1,3-diphenyl-2-propene-1-onate (1) has been synthesized and its crystal structure has been determined. The comparative studies of 1 and its oxygen analog 1,3-diphenyl-1,3-dionate (dibenzoylmethanate) of boron difluoride (2) have been performed using the methods of stationary and time-resolved spectroscopy and quantum chemical modeling. It was established that at the transition from solutions to crystals, a bathochromic shift of the spectra and a significant increase of luminescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Previously we synthesized boron difluoride β‐ketoiminates and studied their luminescence properties . To reveal the relationship between the luminescence properties and the features of the molecular structure of boron difluoride β‐ketoiminates, the range of ligands was extended significantly.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously we synthesized boron difluoride β‐ketoiminates and studied their luminescence properties . To reveal the relationship between the luminescence properties and the features of the molecular structure of boron difluoride β‐ketoiminates, the range of ligands was extended significantly.…”
Section: Resultsmentioning
confidence: 99%
“…Disorder of the quasi‐aromaticity is observed for nitrogen‐containing analogues of boron difluoride dibenzoylmethanate as well . These data allow us to conclude that there is a diene structure in the chelate cycle of boron difluoride β‐ketoiminates …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, di uoroboron β-diketonates exhibit mechanochromic properties [30][31][32] Earlier [33,34], it was shown that the luminescence of concentrated solutions of β-diketonates of boron di uoride was determined by the formation of brightly luminescent aggregates. Here, the low solubility of β-diketonates of boron di uoride with bulky substituents in organic solvents and, as a result, the low concentration of aggregates in solutions leads to the fact that, in most cases no changes are observed in an absorption spectrum of saturated solutions [35][36][37]. Although the evolution of the excitation and luminescence spectra along with an increase of the solution concentration indicates the formation of aggregates in the solution [35][36][37].…”
Section: Introductionmentioning
confidence: 99%